(untitled) (Лучшие интеллектуальные исследования, 2025)
Teaching foreign languages to young learners is a rewarding task that enhances global communication and cultural awareness. To promote effective language learning, educators must adopt approaches tailored to the unique needs and learning styles of children. Young children have an extraordinary ability to learn new languages, and introducing them to a foreign language early can lead to lasting benefits. However, achieving success in this requires thoughtful planning, engaging teaching methods, and a supportive environment. Below, we will explore several strategies for teaching foreign languages to young learners.